PENGARUH METODE INQUIRI TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PELAJARAN IPAS MATERI ORGAN TUBUH MANUSIA DAN HEWAN KELAS V SDN 105268 TELAGA SARI T.A 2023/2024 (JS (JURNAL SEKOLAH), 2024)
Abstract: The purpose of this study was to determine the effect of the inquiry method on critical thinking skills in science lessons on human and animal body organs for grade V of SD Negeri 105268 Telaga Sari Academic Year 2023/2024. This study is a quantitative study with a Quasi Experimental research type. The data collection technique used was a multiple-choice test, the data analysis technique used in this study was the t-test statistical test using SPSS 26. The results of this study indicate that students' critical thinking skills using the inquiry learning method are higher than students' critical thinking skills using conventional learning methods. Statistically, the posttest results of students in the experimental class obtained an average of 76.25 and in the control class an average of 64.50. Thus, the comparison of the average critical thinking skills of different students is 76.25> 64.50. The Independent Sample T-Test test shows Sig. (2- tailed)